Respostas
respondido por:
1
x² - 7x + 10 < 0
x = -b +/- √b² - 4*a*c / 2 * a
x = -(-7) +/- √(-7)² - 4 * 1 * 10 / 2 * 1
x = 7 +/- √49 - 40 / 2
x = 7 +/- √9 / 2
x = 7 +/- 3 / 2
x' = 7 + 3 / 2
x' = 10 / 2
x' = 5
x" = 7-3 / 2
x" = 4 / 2
x" = 2
S={4<x>2}
x = -b +/- √b² - 4*a*c / 2 * a
x = -(-7) +/- √(-7)² - 4 * 1 * 10 / 2 * 1
x = 7 +/- √49 - 40 / 2
x = 7 +/- √9 / 2
x = 7 +/- 3 / 2
x' = 7 + 3 / 2
x' = 10 / 2
x' = 5
x" = 7-3 / 2
x" = 4 / 2
x" = 2
S={4<x>2}
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás